2013
DOI: 10.4236/jep.2013.412165
|View full text |Cite
|
Sign up to set email alerts
|

Potential Groundwater Pollution Risks by Heavy Metals from Agricultural Soil in Songon Area (Abidjan, Côte d’Ivoire)

Abstract: The soil samples were collected taking into account the land use in Songon area. The hydraulic conductivity (K) of soils was characterized in-situ when specific yield (Sy), pHw and concentrations of Cooper, Iron, Zinc, Cadmium, Chromium and Lead were measured in the laboratory. Pollution load indices (PLI) were calculated to evaluate the soil contamination levels. The soils were neutral and alkaline (6.7≤ pH ≤ 9.20), permeable (1.9  10 −5 m•s −1 ≤ K ≤ 8.2  10 −4 m•s −1), with a high specific yield (13.33% ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…To understand the degree of pollution at a particular site, choice of appropriate indices is key and is based on both the risks resulting from their use as well as the purpose for which the pollution indices were developed (Begum et al 2014; Chen et al 2015; Gong et al 2008; Kowalska et al 2016). On farmland soils, understanding the degree of pollution is important for proper environmental management (Kelepertzis 2014; Kouamé et al 2013; Rodríguez et al 2013). Knowledge about soil pollution is important to reduce the risk of environmental exposure and to protect valuable ecosystems (Pan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the degree of pollution at a particular site, choice of appropriate indices is key and is based on both the risks resulting from their use as well as the purpose for which the pollution indices were developed (Begum et al 2014; Chen et al 2015; Gong et al 2008; Kowalska et al 2016). On farmland soils, understanding the degree of pollution is important for proper environmental management (Kelepertzis 2014; Kouamé et al 2013; Rodríguez et al 2013). Knowledge about soil pollution is important to reduce the risk of environmental exposure and to protect valuable ecosystems (Pan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about soil pollution is important to reduce the risk of environmental exposure and to protect valuable ecosystems (Pan et al 2016). Moreover, most agricultural practices (e.g., fertilizer and biocide application) contribute to overall heavy metal enrichment of soil and groundwater (Kouamé et al 2013; Su et al 2014). Hence, considerably disturbed soil can be attributed to multiple sources—natural and anthropogenic.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that there was a high mobility of Cr to depth. According to few research groups [15][16][17], adsorption in the soil allows the retention of the majority of metals on the organic matter very abundant in the surface layers and on the clayed layers. But chromium is not much adsorbed and migrates more towards the deep layers.…”
Section: Heavy Metals Concentrations and Distribution In Soilmentioning
confidence: 99%
“…Accumulation of heavy metals in agricultural soils is instigated by industrial and other human activities such as mining, smelting, cement-pollution, energy and fuel production, power transmission, traffic activities, intensive agriculture, sludge dumping and melting operations [1][2][3][4][5][6][7] . Plants received heavy metals from soils through ionic exchange, redox reactions, precipitation-dissolution, and so on.…”
Section: Introductionmentioning
confidence: 99%